PREVALENCE OF DEPRESSIVE SYMPTOMS IN EMPLOYEES IN A TERTIARY HEALTHCARE INSTITUTION IN BELGRADE DURING THE COVID-19 PANDEMIC - Giljača, Sonja (Acta medicae Medianae, 2023)
Increased work engagement during COVID-19 pandemic has certainly damaged the health of workers in healthcare institutions. The aim of this paper was to determine the quality of life of employees and the presence of depressive symptoms after contracting Covid-19. A panel longitudinal study was conducted (following two times periods in 2020 and 2021 from March to May) among employees at the Belgrade Institute of Neonatology, using the following questionnaires: Patient Health Quality 9 (PHQ-9) for self-assessment of depressive symptoms; EuroQol-visual analogue scale (EQ VAS) for self-assessment of health condition and socio-descriptive characteristics of respondents were collected through a general questionnaire. Only fully completed questionnaires were included in the study, and that number was 138. There were a total of 138 participants (6 men and 132 women). Women were more represented (95.6%) and (66.0%) respondents were married and had a university education. The average value of the score of the PHQ-9 questionnaire for all employees in 2020 was 5.54 + 4.9. We determined that more than half of the employees, 77 (56.0%), had no depressive symptoms, that is, they had a score in the interval of 0-4 points, 30 employees (21.3%) had a score of 5 − 9, 22 employees (16.0%) scored 10 − 14, 7 employees (5.1%) 15 − 19 and score ≥20 had two employees (1.4%). In 2021, average value of the score of the PHQ-9 questionnaire for all employees was 3.8 + 5.12. Without depressive symptoms, there were 70.30% of employees with a score of 0 − 4, which is significantly more (p < 0.01) than in 2020. In all categories, from the mildest subclinical upper score of 5 − 9 to the most severe ≥ 20, depressive symptoms were almost 50% less prevalent among employees in 2021.
Keywords: COVID-19, healthcare workers, symptoms of depression